Nested Climate Accounting for Our Atmospheric Commons—Digital Technologies for Trusted Interoperability Across Fragmented Systems - Schletz, Marco; Hsu, Angel; Mapes, Brendan; Wainstein, Martin (Frontiers in Blockchain, 2022)
The Paris Agreement’s decentralized and bottom-up approach to climate action poses an enormous accounting challenge by substantially increasing the number of heterogeneous national, sub-national, and non-state actors. Current legacy climate accounting systems and mechanisms are insufficient to avoid information asymmetry and double-counting due to actor heterogeneity and fragmentation. This paper presents a nested climate accounting architecture that integrates several innovative digital technologies, such as Distributed Ledger Technology, Internet of Things, machine learning, and concepts such as nested accounting and decentralized identifiers to improve interoperability across accounting systems. Such an architecture can enhance capacity building and technology transfer to the Global South by creating innovation groups, increasing scalability of accounting solutions that can lead to leapfrogging into innovative systems designs, and improving inclusiveness.